Evaluation of the type and frequency of extemporaneous formulations dispensed in hospital and community pharmacies - Zebunnissa Ramtoola; Ayumi Catibusic; Hitam Ameen; Sarah Cullen; James W. Barlow (Exploratory Research in Clinical and Social Pharmacy, 2023)
Background: Extemporaneous compounding is practiced globally by pharmacists to allow for dispensing of personalised doses of medicinal products not commercially available. Extemporaneous compounding must result in a product which is safe and effective. However, data on formulation and expiry of extemporaneous products may not be readily available. Pharmacists access various resources including compounding databases to obtain information on composition, preparation, and expiry of extemporaneous preparations. Objectives: The aim of this study was to evaluate the type and frequency of extemporaneous compounding in hospital and community pharmacies in the Republic of Ireland (ROI) and to obtain contemporary information on compounding practices and resources used. Methods: All community and hospital pharmacists registered with the Pharmaceutical Society of Ireland, were invited to participate in an on-line survey. The study was approved by the Royal College of Surgeons in Ireland (RCSI) research ethics committee. Results: A total of 202 pharmacists responded to the survey, of which 145 were community-based, 52 hospital-based, and 5 practicing in both. On average, hospital and community pharmacists (n = 138) dispensed <2–10 prescriptions for extemporaneous products per month. Pharmacists reported compounding 13 different types of extemporaneous preparations. Of these, dermatological preparations and oral liquid formulations (OLFs) were most commonly compounded. Extemp.ie, an Irish compounding database, was the most frequently used resource for compounding guidance and product expiry. Conclusions: The results of this study show that extemporaneous compounding is still practiced in hospital and community pharmacies in the ROI. The limited response of 4.6% obtained may reflect that extemporaneous compounding is concentrated in a relatively small number of pharmacies. There remains a clinical need for extemporaneous products in the ROI and extemporaneous compounding continues to be an invaluable skillset for pharmacists.